Accountability of Budget Management at the Faculty of Social and Political Sciences, Nusa Cendana University - Long, Belandina L; Seran, Marisa S B; Toda, Hendrik (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates budget management's accountability mechanism and effectiveness at the Faculty of Social and Political Sciences (FISIP) of Nusa Cendana University (UNDANA). A qualitative approach was used to understand the phenomenon, with data collection techniques including interviews, observations, documentation, and focused discussions. Qualitative analysis was conducted to provide a comprehensive understanding of the budget management process at FISIP UNDANA. The study results explain that the accountability mechanism has been well established, and accountability deficits at the program implementer level are identified, with fluctuations in budget absorption from 2020 to 2022. The accountability process is maintained through understanding and reporting the use of public funds and coordination between related parties. Recommendations to improve budget management include training and socialization, strengthening the monitoring system, financial report transparency, and managerial capacity. Further research should focus on comparative analyses between public and private universities, the impact of technological advancements on budget management, longitudinal studies to track changes over time, stakeholder perspectives on accountability practices, and the effectiveness of current policies in enhancing budget management.